The Arab thought and its prospects for the future (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research sheds light on a cultural problem, the contemporary researchers consider as one of the most important problems that contributed to the disintegration of cultural and cognitvevariation in our Arab society that revolves around identifying the cultural identity of this community through the relationship between the old cultural heritage of our society with the contemporary cultural heritage. For this reason, we tried very hard to observe the importance of Arab cultural heritage for the Arab intellectuals who raised the banner of the Islamic Arab Renaissance. They point out, in this context, divergent positions of these thinkers of the heritage among Salafi stream strongly advocates adherence to heritage and benefit from it, the contemporary stream calls to go about European modern thinking and go away from the heritage, and the third stream calls for taking cultural and cognitive aspects of the right of the Salafi and contemporary currents -that is, between tradition and modernity with reference to the most important factors that contributed to the failure of the Arab cultural renaissance project.